2013
DOI: 10.1111/jonm.12130
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of regulated nurses' intention to stay in long-term care homes

Abstract: To retain qualified nursing staff and ensure quality of care, long-term care administrators should focus on creating a work environment that reduces burnout, increases job satisfaction, and enables nurses to foster relationships with residents. Recommendations for long-term care administrators include: (1) provide opportunities for self-scheduling, full-time work and benefits; (2) develop models of care that enhance resident relationships; (3) examine existing regulated nursing staff responsibilities and adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 34 publications
3
55
2
Order By: Relevance
“…Job satisfaction was not found to be associated with delaying retirement. This may be due to using the word “retirement” in the present study rather than the more inclusive broader terms “retention” (Blake, Leach, Robbins, Pike, & Needleman, ), “intent to stay,” “intent to leave” (McGilton, Tourangeau, Kavcic, & Wodchris, ) and “nurse turnover” (Currie & Carr Hill, ). This may also indicate that job satisfaction is not as important when studying delayed retirement, as opposed to retention.…”
Section: Discussionmentioning
confidence: 98%
“…Job satisfaction was not found to be associated with delaying retirement. This may be due to using the word “retirement” in the present study rather than the more inclusive broader terms “retention” (Blake, Leach, Robbins, Pike, & Needleman, ), “intent to stay,” “intent to leave” (McGilton, Tourangeau, Kavcic, & Wodchris, ) and “nurse turnover” (Currie & Carr Hill, ). This may also indicate that job satisfaction is not as important when studying delayed retirement, as opposed to retention.…”
Section: Discussionmentioning
confidence: 98%
“…We found only a few studies that focused on intent to stay. Intent to stay is defined as a nurse's decision to stay in their area of practice or profession (McGilton, Tourangeau, Kavcic, & Wodchis, ). In a descriptive study using focus groups, a number of determinants were found that influenced a nurse's intent to stay (Tournageau, Cummings, Cranley, Ferron, & Harvey, ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…This may be due to the frequency of deaths and the importance of direct care on physically dependent residents affected by severe chronic diseases (Blanchard et al., ; Gosseries et al., ). Psychological implications of burnout for the caregiver may lead to absenteeism, job withdrawal, depression or suicide (Dyrbye et al., ; McGilton, Tourangeau, Kavcic, & Wodchis, ; Piers et al., ). Burnout can have significant consequences on the quality of care, as it has been described to directly impact patient mortality (Wallace, Lemaire, & Ghali, ).…”
Section: Introductionmentioning
confidence: 99%